Evaluación de los cambios de coloración vulvar y temperatura rectal, asociadas con la presencia de células epiteliales vaginales durante el ciclo estral en hembras bovinas de la Universidad Técnica de Babahoyo - Chávez Gordillo, Diego Salomon (2016)
SUMMARY This research dealt with the evaluation of vulvar changes color and rectal temperature, associated with the presence of vaginal epithelial cells during the estrous cycle in bovine females of the Technical University of Babahoyo. Livestock was held in the Faculty of Agricultural Sciences, located at km 7 of the road Babahoyo Montalvo Los Rios Province, at a height of 7.5 m whose geographical coordinates is of 79º west longitude and 01º 32`de 49 `south latitude. It presents tropical climate characterized by an annual average temperature of 25 ° C, with relative humidity of 76% and rainfall of 2791.4 mm / year. The objectives were to evaluate the characteristics of vulvar staining and rectal temperature as an indicator of vaginal cytology, set the percentage of vaginal epithelial cells in relation to temperature and vulvar coloration in the estrous cycle. Animals were sampled only in the morning (84 days), and the data were evaluated by nonparametric descriptive statistics. The results, vaginal epithelial cells that had highest percentage were cornified cells, while other cell types were presented at low percentages throughout the study time. The temperature was maintained between 38 and 38.5 estrus except that when the temperature was raised to 39.5 ° C and the vulvar pale colouration remained and pink, reaching turn red in estrus. It could also be analyzed that there is a relationship between age and percentage of cornified cells, ie the older higher percentage of cornified cells (60%).